Interrelationship between copper and bovine health - Larson, Robert L.; Arthington, J.D.; Corah, L.R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Trace mineral nutrition is important to production efficiency and animal health. Trace mineral imbalances may be the roots of many diagnosed or undiagnosed problems in a herd. The low cost of a complete mineral analysis when compared to production losses encourages its use in the evaluation of any bovine herd in which trace mineral imbalances are suspected. A systematic gathering of information on mineral intake, antagonist intake, and serum and tissue values is necessary in order to make a diagnosis and a rational treatment decision. It is important to understand the complex interactions between minerals so that supplementation with one element does not make a complicated situation worse. Because of the many interactions between nutrients and the cost of mineral supplements, recommending use of higher levels of trace minerals in a ration or supplement without a complete diagnosis is economically and nutritionally unjustified.
Keywords: Beef; Copper; Trace minerals; Immune function